Multisystem Involvement Induced by Human Parvovirus B19 Infection in a Non-immunosuppressed Adult: A Case Report - Zou, Qihang; Chen, Peisong; Chen, Jiaxin; Chen, Dingbang; Xia, Han; Chen, Ling; Feng, Huiyu; Feng, Li (Frontiers in Medicine, 2022)
Background: Human parvovirus B19 (B19V) infection is usually symptomless and occurs in the childhood. While in immunocompromised adults, B19V infection also presents various clinical symptoms due to the host's immune status. The classic symptoms include erythema, anemia, arthropathy, and edema, but neurological involvement is rare. Case presentation: In this report, we present a case of B19V infection caused multiple organ dysfunction in a non-immunosuppressed adult. Metagenomic next-generation sequencing (mNGS) was used and successfully detected the pathogen in multiple types of samples, including blood, cerebrospinal fluid (CSF), and bronchoalveolar lavage fluid (BALF). The diagnosis was subsequently confirmed by polymerase chain reaction (PCR). He was treated with intravenous gamma globulin, resulting in a significant resolution of symptoms after 1 month. Conclusion: Multisystem involvement induced by B19V infection was found in this case report. mNGS performed great advantages in rapidly and accurately diagnosing B19V infection in multiple types of samples, which helps the timely adjustment of treatment and improves the prognosis.